The Poison Dictates the Antidote: An Evaluation of a Rehabilitation Service for Torture Survivors Seeking International Protection in Ireland - Hearns, Aisling Fiona (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2023)
Background: The growing number of refugees is of particular concern to global mental health practitioners. Specifically, rates of torture among forced migrants are thought to exceed 50% (Duffy & Kelly, 2015). Survivors of torture often face challenges in accessing holistic rehabilitation, and psychological testing in this context is underexplored. The introduction of Complex PTSD (CPTSD) in the ICD-11 and the IRCT Global Standards in 2022 offer new avenues for research in trauma treatment. Objectives: These gaps in knowledge were explored through three research objectives.:1) To explore whether the ICD-11 aligned ITQ is a suitable measure for trauma disorders with a population of torture survivors seeking international protection; 2) To establish if engaging with torture rehabilitation services is associated with changes in psychological wellbeing, and if so, is this change mediated by (i) higher levels of engagement with a holistic rehabilitation programme and/or (ii) a perceived sense of control; and 3) To understand whether, and if so, how survivors of torture perceive rehabilitation services as having contributed to their rehabilitation. Methods: Underpinned by a pragmatist approach, this body of work adopted a sequential, mixed-methods design, carried out in two phases. Participants attended a torture rehabilitation centre in Ireland called Spirasi. Phase One consisted of quantitative research to address Research Objectives 1 and 2. Phase Two then consisted of a qualitative approach to address Objective 3. Objective 1 was achieved through a secondary data analysis (N = 264), using ITQ questionnaires collected between 2016 and 2018. Confirmatory factor analysis was used to assess the symptom structure of the PTSD/CPTSD symptoms. Objective 2 was achieved through a secondary data analysis of mental health indictor scores during initial assessment (N=75) and a review assessment >12 months after intake (N=54). A paired sample t-test was used to test whether there are significant changes in mental health indictor scores changed over time, and a mediation analysis was used to establish if change in mental health indictors were mediated by level of engagement in a holistic model of rehabilitation and sense of control (Lachman & Weaver, 1998). Objective 3 was achieved through a series of qualitative interviews (N=22) conducted with service-users who had engaged in Spirasi?s services for >12 months. Key Findings: ICD-11 diagnoses of PTSD and CPTSD, as measured by the ITQ, were successfully validated for use with a cross-cultural group of treatment-seeking torture survivors who were seeking international protection in a Western host country (i.e., Ireland). Findings showed high levels of psychopathology across all mental health indictors and a significant reduction in PTSD between Time 1 and Time 2. Level of engagement in Spirasi services were low across all strands of Spirasi's holistic model and failed to show any mediation impact. A sense of control was shown to be a mediating factor for the reduction in depression symptoms. Findings from Phase Two yielded key themes of power, control, and uncertainty and the need to be countered and included in the rehabilitation approach i.e., empowerment, choice, and certainty. Taken together, results of all three studies are synthesised to propose a new model for rehabilitation for survivors of torture seeking international protection: The Survivors Model for Rehabilitation. Implications of this research are discussed with the consideration of the current context in Ireland and globally with particular attention to how these findings contribute to theory, practice and policy, on a local, national and international level. Limitations and potential areas for further research are discussed, and recommendations are made to improve current practices for the rehabilitation of torture survivors.
APPROVED
Keywords: Torture; Rehabilitation; Refugee; Trauma; Complex Trauma; PTSD; CPTSD